2008
DOI: 10.1016/j.neuropsychologia.2008.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of the curvature aftereffect in dynamic touch

Abstract: a b s t r a c tA haptic curvature aftereffect is a phenomenon in which the perception of a curved shape is systematically altered by previous contact to curvature. In the present study, the existence and intermanual transfer of curvature aftereffects for dynamic touch were investigated. Dynamic touch is characterized by motion contact between a finger and a stimulus. A distinction was made between active and passive contact of the finger on the stimulus surface. We demonstrated the occurrence of a dynamic curv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
36
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(45 citation statements)
references
References 30 publications
8
36
1
Order By: Relevance
“…Strength of the after-effect is defined as follows: 100 % Â (PSE after adaptation to a convex stimulus minus PSE after adaptation to a concave stimulus)/(convex minus concave adaptation curvature). Data from various studies combined and reanalysed: (a) Same hand or finger conditions: hand static [9,12], hand dynamic [12], five fingers static [12], one finger static [18], one finger active [16]; (b) Transfer to other hand or finger: hand static [12], finger static [18], finger active [16], finger passive [16]; (c) Different conditions with the same hand or finger: hand dynamic-static and hand static-dynamic [12], finger active-passive and finger passive-dynamic [16]; (d ) From hand to fingers and vice versa [12]. The numbers in the bars indicate the number of subjects that participated in an experiment.…”
Section: (B) Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strength of the after-effect is defined as follows: 100 % Â (PSE after adaptation to a convex stimulus minus PSE after adaptation to a concave stimulus)/(convex minus concave adaptation curvature). Data from various studies combined and reanalysed: (a) Same hand or finger conditions: hand static [9,12], hand dynamic [12], five fingers static [12], one finger static [18], one finger active [16]; (b) Transfer to other hand or finger: hand static [12], finger static [18], finger active [16], finger passive [16]; (c) Different conditions with the same hand or finger: hand dynamic-static and hand static-dynamic [12], finger active-passive and finger passive-dynamic [16]; (d ) From hand to fingers and vice versa [12]. The numbers in the bars indicate the number of subjects that participated in an experiment.…”
Section: (B) Resultsmentioning
confidence: 99%
“…The data of four studies of haptic after-effects will be presented, compared and discussed [9,12,16,18]. As these studies have large parts of their procedures in common, these will be described together.…”
Section: Haptic After-effect Of Curved Surfacesmentioning
confidence: 99%
“…This phenomenon was later examined by Vogels et al [19], who found a curvature aftereffect when observers explored curved surface under whole-hand, direct-touch static conditions. Indeed, haptic aftereffects have been observed in various touch exploration modes, both static [19], [20] and dynamic [21].…”
Section: Introductionmentioning
confidence: 99%
“…Further, van der Horst et al also found that the curvature aftereffect transferred between hands during both passive [20] and active [21] modes of exploration, suggesting that curvature information may also be represented at a stage in the somatosensory cortex shared by the fingers of both hands, involving several levels of neural processing. In addition, a larger aftereffect in active exploration compared to passive exploration suggests the importance of selfinduced movement [21], which in turn suggests that representation depends on the exploration mode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation